2009
DOI: 10.1093/jac/dkn541
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of linezolid in patients with major thermal injuries

Abstract: The pharmacokinetics of linezolid are altered in patients with major thermal injuries, mainly as a result of increased non-renal clearance. These changes are of sufficient magnitude that linezolid concentrations may be sub-therapeutic in some patients and we suggest that the dosage interval may need to be decreased in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Indeed, although median values for C min , C max , and AUC 24 were similar to those observed in healthy volunteers (17,32), their ranges were significantly wider.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Indeed, although median values for C min , C max , and AUC 24 were similar to those observed in healthy volunteers (17,32), their ranges were significantly wider.…”
Section: Discussionsupporting
confidence: 65%
“…This could be especially true for patients with severe burn injuries and/or with cystic fibrosis, in whom linezolid clearance was recently shown to be significantly increased (4,10,17,30). Interestingly, in patients with cystic fibrosis, among the various mechanisms that could be responsible for the well-known enhanced clearance of antimicrobial drugs, it has been suggested that the overexpression of P-gp may play a major role (30,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is primarily attributed to increased nonrenal clearance. For patients with very extensive or complicated burns, where interpatient variability is large, insuffi cient drug exposure may occur (Lovering et al 2009 ). Other clinical studies with critically ill patients confi rm the increased volume of distribution and clearance Buerger et al 2006 ;Boselli et al 2005 ).…”
Section: Critically Ill Patientsmentioning
confidence: 99%
“…In the case of linezolid, resistance is usually associated with a point mutation at the drug target site at position 2576 of 23S rRNA. However, other mutations have been found in clinical isolates (Lovering et al 2009 ) or selected for in serial passage experiments (Locke et al 2009 ). Most bacteria have several copies of rRNA genes and signifi cant resistance requires mutations in more than one copy of the 23S rRNA gen. MICs increase in proportion to the number of copies of mutant 23S rRNA genes (Livermore et al 2009 ).…”
Section: Resistancementioning
confidence: 99%